Assessing small RNA profiles in potato diploid hybrid and its resynthesized allopolyploid reveals conserved abundance with distinct genomic distribution - Leone, Melisa (Springer, 2024)
Allopolyploidy, a complex process involving interspecific hybridization and whole genome duplication, significantly impacts plant evolution, leading to the emergence of novel phenotypes. Polyploids often present phenotypic nuances that enhance adaptability, enabling them to compete better and occasionally to colonize new habitats. Whole-genome duplication represents a genomic “shock” that can trigger genetic and epigenetic changes that yield novel expression patterns. In this work, we investigate the polyploidization effect on a diploid interspecific hybrid obtained through the cross between the cultivated potato Solanum tuberosum and the wild potato Solanum kurtzianum, by assessing the small RNAs (sRNAs) profile of the parental diploid hybrid and its derived allopolyploid. Small RNAs are key components of the epigenetic mechanisms involved in silencing by RNA-directed DNA Methylation (RdDM). A sRNA sequencing (sRNA-Seq) analysis was performed to individually profile the 21 to 22 nucleotide (21 to 22-nt) and 24-nt sRNA size classes due to their unique mechanism of biogenesis and mode of function. The composition and distribution of different genomic features and differentially accumulated (DA) sRNAs were evaluated throughout the potato genome. We selected a subset of genes associated with DA sRNAs for messenger RNA (mRNA) expression analysis to assess potential impacts on the transcriptome. Interestingly, we noted that 24-nt DA sRNAs that exclusively mapped to exons were correlated with differentially expressed mRNAs between genotypes, while this behavior was not observed when 24-nt DA sRNAs were mapped to intronic regions. These findings collectively emphasize the nonstochastic nature of sRNA remobilization in response to the genomic shock induced by allopolyploidization.
Keywords: Ciencias agrícolas::Biotecnología agrícola::Biotecnología agrícola y biotecnología alimentaria